Naturally Abundance Vanillin as Starting Material to Synthesizing 4-(4-Hydroxy-3-methoxyphenyl)-6-methyl-3,4-dihydropyrimidin-2(1H)-one - Masruri MASRURI; Yuga Adi Pranata (Chemistry Department, The University of Brawijaya, 2015)
Indonesia is the second biggest producer of natural vanillin. Traditionally it was isolated from the bean of vanilla (Vanilla planifolia Andrews). This paper reports on applying vanillin as starting material for synthesizing a biologically important chemical structure 3,4-dihydropyrimidinone. The reaction was undertaken in one step following multi component reaction (MCR). Products determination was undergone using FTIR and UV-Vis spectrophotometry, and also liquid chromatography-mass spectrometry (LCMS). After purification under flash column chromatography in ethyl acetate-hexane, it was found a white solid of 4-(4-hydroxy-3-methoxyphenyl)-6-methyl-3,4-dihydropyrimidin-2(1H)-one in 67% yield with a few amount of an unreacted vanillin.